Regulation of Electronic Notarial Deed Creation in Indonesia Based on the Principle of Legal Certainty: Between Opportunities and Challenges - Yusakawati, Ni Made Arya Dwi; Sudiro, Amad (Jurnal Daulat Hukum, 2025)
Notaries, entrusted with upholding legal certainty by producing authentic legal documents, now face notable difficulties in adapting to digital transformation. Even though electronic transactions and forms of digital authentication have become more widely embraced, Indonesia still lacks a clear legal framework for electronic notarial deeds (e-notary), resulting in legal uncertainty regarding their authenticity, validity, and evidentiary strength within the national legal system. Accordingly, this study raises two central problems: (1) how relevant are the elements “before a public official” and “made at the place where the deed is made” under Article 1868 of the Indonesian Civil Code within the context of electronic notarial deeds, and (2) what are the opportunities and challenges in regulating electronic notarial deeds to ensure authenticity and legal certainty. This study analyzes two central problems as previously mentioned. The research employs a normative legal method with statutory and conceptual approaches. The findings reveal that the elements of authenticity in deeds as stipulated in Article 1868 of the Indonesian Civil Code and the Notary Office Law still emphasize physical presence; however, in the digital era, they must be reinterpreted functionally through electronic communication systems that ensure security, integrity, and the free will of the parties. The digitalization of notarial systems presents opportunities for efficiency, transparency, and institutional integration, but it also faces normative, technical, and ethical challenges that require regulatory reconstruction and strengthening of digital legal infrastructure. Legal reform through the amendment of the Notary Office Law, establishment of implementing regulations, and adoption of blockchain technology are essential to ensure legal certainty in the implementation of electronic notarial deeds in Indonesia.